Fused Deposition Modeling 3D Printing of Continuous Natural and Regeneration Fibers Reinforced Polymer Composites and Its Mechanical Properties under Extreme Environmental Conditions—A Critical Review - Jinlong Zhang; Qinglin Wu; Cornelis F. De Hoop; Shulin Chen; Ioan Negulescu (BioResources)
Continuous fiber 3D printing, as a new technology, has attracted attention in an increasing number of applications. Research on continuous fiber 3D printing is currently still in its infancy, after less than 10 years since its discovery in 2016. Many technical and fundamental questions still need to be addressed. Most literature has dealt with 3D printing employing continuous synthetic fibers (e.g., carbon and aramid fibers). This critical review summarizes the progress on the 3D printing of continuous natural plant fibers and their regenerated fibers and their use in reinforced thermoplastic composites. Their mechanical performance under extreme environmental conditions is further reviewed. These high-performance continuous fiber reinforced polymer composites have potential for high value applications such as aerospace technologies.